Nomadic New Women
XV, 362 p. 3 illus., 1 illus. in color.
Keywords: Nomadic New Women: Exile and Border-Crossing between Spain and the Americas, Early to Mid-Twentieth Century examines how gender and sexuality, border-crossing and exile intersect in women’s intellectual and artistic practices during the volatile historical period of the first half of the twentieth century, in and around Spain and the Americas. Each of the twelve chapters in this highly interdisciplinary volume analyzes the combined impact of gender and sexual identity, and the traversing of particular national and world-regional boundaries, on creative work. Together and separately, the contributors push the limits of past and present research on exile and migration, displacement and nomadism to reveal how the complex interrelationships among gender, sexuality, and cultural production come under intense pressure by the crossing of borders. Renée M. Silverman is Associate Professor of Spanish, Florida International University, USA. She is author of Mapping the Landscape, Remapping the Text: Spanish Poetry from Antonio Machado’s Campos de Castilla to the First AvantGarde (1909–1925) (2014), and editor/co-editor of The Popular Avant-Garde (2010) and Mediterranean Modernism: Intercultural Exchange and Aesthetic Development (2016). Esther Sánchez-Pardo is Professor of English at Complutense University of Madrid, Spain. She is author of Cultures of the Death Drive (2003) and Mina Loy. Anthology (2009), editor of Poéticas Comparadas de Mujeres (2022), and coeditor of Women Poets and Myth in the 20th and 21st Centuries (2018) and Myth and Environmentalism (2023).